THE EFFECT OF RECENT VENUS TRANSIT ON EARTH'S ATMOSPHERE - De S.S.; Adhikari S.K.; Sarkar B.K.; Guha A.; Mandal P.K.; Mandal S.K.; Sardar H.P.; Ray M.; De B.K.; Sarkar S.K. (My University, 2006)
Some experiments on June 8, 2004, the day of transit of Venus across the Sun, were undertaken at Kolkata (latitude: 22°34′N) to observe the effect, if any, of transit of Venus on FWF, ELF and VLF amplitudes. The result shows a good correlation between their temporal variations during the transit. The observation was unbelievable as the Venus subtends only 1/32th of the cone subtended by Sun on Earth. This anomaly may be explained on the assumption that the height of Venusian atmosphere with high content of CO2, and nitrogen which absorbs electromagnetic and corpuscular radiations from Sun, depleting the solar radiation reaching the Earth to a considerable extent. As a result, relevant parameters of Earth's atmosphere are modulated and here we show how these changes are reflected in identical behaviour of fair weather field and ELF and VLF spectra.
Keywords: EFFECTS ON ATMOSPHERIC ELECTRIC PARAMETERS; VENUS TRANSIT